2021
DOI: 10.3390/jcm10071528
|View full text |Cite
|
Sign up to set email alerts
|

Nailfold Capillaroscopy in Systemic Sclerosis Patients with and without Pulmonary Arterial Hypertension: A Systematic Review and Meta-Analysis

Abstract: Systemic sclerosis (SSc)-related pulmonary arterial hypertension (SSc-PAH) is a leading cause of mortality in SSc. The extent of peripheral microvasculopathy assessed through nailfold capillaroscopy might correlate with the presence of PAH in SSc patients. We searched the PubMed, Cochrane Library, Scopus, and Web of Science databases and performed a random effects meta-analysis of observational studies comparing nailfold capillaroscopic alterations in SSc-PAH versus SSc-noPAH patients. Weighted mean difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 55 publications
3
19
0
Order By: Relevance
“…In addition, low capillary density correlates directly with mean pulmonary pressure. Overall, our findings provide additional evidence to the literature data, confirming that a higher degree of peripheral nailfold microangiopathy is more common in SSc-PAH patients, and further strengthening the concept that NVC changes may run parallel with similar abnormalities inside pulmonary microcirculation ( 23 , 24 ). If confirmed by further investigations in larger patients' series, NVC microvascular alterations could be included in the armamentarium of PAH early detection and so to contribute to a better survival of the patients.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In addition, low capillary density correlates directly with mean pulmonary pressure. Overall, our findings provide additional evidence to the literature data, confirming that a higher degree of peripheral nailfold microangiopathy is more common in SSc-PAH patients, and further strengthening the concept that NVC changes may run parallel with similar abnormalities inside pulmonary microcirculation ( 23 , 24 ). If confirmed by further investigations in larger patients' series, NVC microvascular alterations could be included in the armamentarium of PAH early detection and so to contribute to a better survival of the patients.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies demonstrated some correlations between NVC abnormalities and the severity of internal organs involvement, including PAH (20,23,24,30,31). In a 3year prospective study, the sequential loss of capillaries was recognized as a marker for the occurrence of PAH (31).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…"Abnormal nailfold capillaries" (when referring to the "scleroderma pattern") are included in the 2013 American College of Rheumatology (ACR)/ European League Against Rheumatism (EULAR) classification criteria for SSc (11). Cumulative data suggest that NVC measurements can serve as a reliable marker of the extent and severity of microvasculopathy in different vascular districts such as pulmonary (12) and myocardial microcirculation (13) to the point that NVC is currently considered as a surrogate marker of SSc progression (14). However, the association between UA and NVC changes in SSc has not been well-established.…”
Section: Introductionmentioning
confidence: 99%